A quaternized cellulose-based resin and its preparation method and application
The preparation method of quaternized cellulose-based resin solves the problem of traditional resin materials using toxic reagents and organic solvents when removing PFAS, achieving a green and efficient removal effect. The resin is easy to recycle and is suitable for large-scale production.
Patent Information
- Application Number
- CN202410545679.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-30
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-04-30
AI Technical Summary
When removing perfluoroalkyl and polyfluoroalkyl substances (PFAS) in water, existing amination resin materials need to use toxic reagents and react in organic solvents, which poses environmental protection and safety risks.
The preparation method of quaternized cellulose-based resin is adopted, by mixing the cellulose solution with sodium hydroxide, urea and water, pre-cooling and high-speed mixing, and then mixing it with 3-chloro-2-hydroxypropyltrimethylammonium chloride. The aqueous solution undergoes a quaternization reaction and reacts with chlorine balls at high temperature to obtain a quaternized cellulose-based resin. This method is environmentally friendly and does not use toxic reagents.
It achieves effective removal of perfluorinated substances in drinking water, has excellent adsorption performance, and can meet my country's latest "Drinking Water Hygienic Standards". At the same time, the resin is easy to recycle, solving the problem of difficult recycling of powder adsorbents.
Smart Images

Figure CN118459777B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new material preparation, and specifically relates to a quaternized cellulose-based resin and a preparation method and application thereof. Background Art
[0002] Per- and polyfluoroalkyl substances (PFAS) have been widely used in manufacturing and consumer products for decades, but are now of global concern as priority pollutants, with more than 1,400 chemicals listed on the Toxic Substances Control Act Inventory. As concerns have grown about the ecological persistence, accumulation, and health hazards of PFASs, the most widely used long-chain PFASs (chain length > 7), perfluorooctane sulfonate and perfluorooctanoate, have been restricted in their production and use under the Stockholm Convention.
[0003] The development of effective remediation methods to remove these compounds has attracted the attention of the public and the scientific community. Among the many proven remediation methods, adsorption is the simplest and most cost-effective method for removing PFAS. Currently, aminated resin materials are widely used for the adsorption of PFAS in water. These resin materials can adsorb PFAS through electrostatic effects and are easy to recover from water, making them convenient for large-scale applications. However, traditional aminated resin materials usually require organic amine reagents to react with chlorine balls, and the entire reaction process needs to be carried out in an organic system, such as chlorine balls such as benzene, ethylene dichloride, carbon tetrachloride and acetone. Summary of the invention
[0004] The purpose of the present invention is to provide a quaternized cellulose-based resin and a preparation method and application thereof. The preparation method provided by the present invention is green and environmentally friendly and does not use toxic reagents.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The invention provides a method for preparing a quaternary ammonium cellulose-based resin, comprising the following steps:
[0007] (1) mixing a cellulose solution, sodium hydroxide, urea and water, and then precooling and high-speed mixing in sequence to obtain a cellulose solution; the rotation speed of the high-speed mixing is 500 to 1000 rpm;
[0008] (2) mixing an aqueous solution of 3-chloro-2-hydroxypropyltrimethylammonium chloride and the cellulose solution to carry out a quaternization reaction to obtain a quaternized cellulose solution;
[0009] (3) The quaternary ammonium cellulose solution and chlorine balls are mixed for high temperature reaction, wherein the particle size of the chlorine balls is 0.315 to 1.250 mm and the temperature of the high temperature reaction is 100 to 150° C. to obtain a quaternary ammonium cellulose-based resin.
[0010] Preferably, the cellulose solution comprises cellulose and water; the mass ratio of cellulose to urea in the cellulose solution is 1:25-100; the mass ratio of cellulose to sodium hydroxide in the cellulose solution is 1:25-100; and the mass ratio of urea to water is 1:2-11.
[0011] Preferably, the precooling temperature is -10 to -50°C, and the insulation time is 1 to 5 hours.
[0012] Preferably, the molar ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride in the 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution to cellulose units in the cellulose solution is 5 to 50:1.
[0013] Preferably, the temperature of the quaternization reaction is 20 to 50° C., and the insulation time is 12 to 20 hours.
[0014] Preferably, the mass ratio of the chlorine balls to the quaternized cellulose is 1 to 10:1.
[0015] Preferably, the insulation time of the high temperature reaction is 10 to 15 hours.
[0016] The present invention also provides a quaternary ammonium cellulose-based resin obtained by the preparation method described in the above scheme, comprising chlorine balls and quaternary ammonium cellulose modified on the surface of the chlorine balls.
[0017] Preferably, the mass ratio of the chlorine balls to the quaternary ammonium cellulose is 1 to 10:1.
[0018] The present invention also provides the use of the quaternary ammonium cellulose-based resin described in the above scheme in water purification.
[0019] The present invention provides a method for preparing a quaternary ammonium cellulose-based resin. The present invention functionalizes cellulose extracted from traditional Chinese medicine waste residues and then grafts it onto the surface of a chlorine ball. The obtained quaternary ammonium cellulose-based resin is easy to recycle and can be mass-produced, which solves the problem that powder adsorbents are difficult to recycle. It also has good stability and excellent removal ability for perfluorinated substances in drinking water. Compared with traditional aminated resin synthesis, the preparation method provided by the present invention does not use toxic reagents, and the synthesis process is green, environmentally friendly, and low-cost. It achieves harmless disposal and resource utilization of solid waste while effectively preventing and controlling PFAS pollution to ensure the safety of drinking water.
[0020] The present invention uses cellulose as a raw material. Cellulose is one of the most abundant biopolymers on earth, has low toxicity and biocompatibility, is rich in hydroxyl groups on its surface, is low in cost, and is green and environmentally friendly.
[0021] The present invention also provides a quaternized cellulose-based resin obtained by the preparation method described in the above scheme, including a chlorine ball and a quaternized cellulose modified on the surface of the chlorine ball. The quaternized cellulose-based resin provided by the present invention is easy to separate from water and easy to recycle, which solves the problem that the powder adsorbent is difficult to recycle, and has good stability, can be produced on a large scale, has excellent removal ability for perfluorinated substances in drinking water, can effectively remove trace perfluorinated substances in drinking water, effectively prevent and control PFAS pollution, and ensure the safety of drinking water.
[0022] The present invention also provides the use of the quaternized cellulose-based resin described in the above scheme in water purification. The quaternized cellulose-based resin provided by the present invention can effectively remove perfluorinated substances (PFAS) in water, especially drinking water, such as perfluorooctanoic acid (PFOA) and perfluorooctane sulfonic acid (PFOS), meeting the latest "Sanitary Standards for Drinking Water" in my country. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 The scanning electron microscope images of the original chlorine ball (a) and the quaternized cellulose-based resin (b) in Example 1 of the present invention;
[0025] Figure 2 The infrared spectra of the original chlorine balls and the quaternized cellulose-based resin in Example 1 of the present invention are shown;
[0026] Figure 3 The effect diagram of removing PFAS by the original chlorine balls and quaternized cellulose-based resin in Example 1 of the present invention and the quaternized resin prepared in Comparative Example 4;
[0027] Figure 4 The quaternary ammonium cellulose-based resins obtained by using different ratios of quaternary ammonium salts and cellulose units in comparative examples 1 to 3 are shown in the figure for removing PFAS;
[0028] Figure 5 This is a kinetic diagram of the removal of perfluorooctanoic acid (a) and perfluorooctane sulfonic acid (b) by the quaternary ammonium cellulose-based resin prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The invention provides a method for preparing a quaternary ammonium cellulose-based resin, comprising the following steps:
[0030] (1) mixing a cellulose solution, sodium hydroxide, urea and water, and then precooling and high-speed mixing in sequence to obtain a cellulose solution; the rotation speed of the high-speed mixing is 500 to 1000 rpm;
[0031] (2) mixing an aqueous solution of 3-chloro-2-hydroxypropyltrimethylammonium chloride and the cellulose solution to carry out a quaternization reaction to obtain a quaternized cellulose solution;
[0032] (3) The quaternary ammonium cellulose solution and chlorine balls are mixed for high temperature reaction, wherein the particle size of the chlorine balls is 0.315 to 1.250 mm and the temperature of the high temperature reaction is 100 to 150° C. to obtain a quaternary ammonium cellulose-based resin.
[0033] The present invention mixes cellulose solution, sodium hydroxide, urea and water, and then precools and mixes at high speed in sequence to obtain a cellulose solution. In the present invention, the preparation method of the cellulose solution is preferably: obtain Chinese medicine waste residue cellulose with reference to Chinese patent CN 117144707 A, and mix the obtained Chinese medicine waste residue cellulose with water (recorded as the first mixing). The present invention removes lignin and hemicellulose by a one-step potassium persulfate (PMS) heating method to obtain Chinese medicine waste residue cellulose.
[0034] In the present invention, the raw material of the Chinese medicine waste residue cellulose is Chinese medicine waste residue; the Chinese medicine waste residue preferably includes one or more of red peony root, Chinese rhizoma cyperi and Chinese radix scutellariae.
[0035] In the present invention, the first mixing is preferably ultrasound; the power of the ultrasound is preferably 1000-1200 W, and the ultrasound time is preferably 10-30 min. The present invention obtains a uniformly dispersed cellulose solution through short-term high-power ultrasound treatment.
[0036] In the present invention, the water is preferably distilled water.
[0037] In the present invention, the mass ratio of cellulose to urea in the cellulose solution is preferably 1:25-100, more preferably 1:40-90, and further preferably 1:50-80.
[0038] In the present invention, the mass ratio of cellulose to sodium hydroxide in the cellulose solution is preferably 1:25-100, more preferably 1:30-90, and further preferably 1:35-70.
[0039] In the present invention, the mass ratio of urea to water is preferably 1:2-11, more preferably 1:3-10, and further preferably 1:4-8.
[0040] In the present invention, the precooling temperature is preferably -10 to -50°C, more preferably -15 to -30°C, further preferably -20°C, and the insulation time is preferably 1 to 5h, more preferably 2 to 4h, further preferably 3h; the precooling equipment is preferably a refrigerator.
[0041] In the present invention, the precooling is preferably followed by rapid high-speed mixing; the high-speed mixing is preferably high-speed stirring; the temperature of the high-speed stirring is preferably 25 to 45°C, more preferably 30 to 40°C, further preferably 35°C, and the stirring time is preferably 5 to 30 min, more preferably 10 to 20 min, further preferably 15 min.
[0042] After obtaining the cellulose solution, the present invention mixes the 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution and the cellulose solution (referred to as the second mixing) to carry out a quaternization reaction to obtain a quaternized cellulose solution. In the present invention, the molar ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride in the 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution to the cellulose unit in the cellulose solution is preferably 5 to 50:1, more preferably 10 to 45:1, and further preferably 20 to 40:1.
[0043] In the present invention, the second mixing is preferably: stirring (referred to as the second stirring) the cellulose solution, while dropping 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution into the cellulose solution and continuing stirring (referred to as the second stirring).
[0044] In the present invention, the dripping rate is preferably 30 to 90 drops / minute, more preferably 40 to 80 drops / minute; the second stirring rate is preferably 300 to 800 rpm, more preferably 400 to 600 rpm.
[0045] In the present invention, the temperature of the quaternization reaction is preferably 25 to 50° C., more preferably 35 to 40° C., and the insulation time is preferably 12 to 20 h, more preferably 16 h.
[0046] After obtaining the quaternary ammonium cellulose solution, the present invention mixes the quaternary ammonium cellulose solution and chlorine balls for high-temperature reaction, wherein the particle size of the chlorine balls is 0.315 to 1.250 mm, and the temperature of the high-temperature reaction is 100 to 150° C., to obtain a quaternary ammonium cellulose-based resin. In the present invention, the mass ratio of the chlorine balls to the quaternary ammonium cellulose is preferably 1 to 10:1, more preferably 2 to 8:1, and further preferably 3 to 6:1.
[0047] In the present invention, the particle size of the chlorine ball is preferably 0.35 to 1.25 mm, more preferably 0.45 to 1.25 mm, and further preferably 0.63 to 1.25 mm.
[0048] In the present invention, the temperature of the high temperature reaction is preferably 105-145°C, more preferably 110-140°C, further preferably 115-130°C, and the insulation time is preferably 10-15h, more preferably 11-14h, further preferably 12-13h.
[0049] In the present invention, the high temperature reaction preferably further comprises post-processing the obtained product; the post-processing preferably comprises: soaking, washing and drying the obtained product in sequence.
[0050] In the present invention, the soaking time is preferably 3 to 8 hours, more preferably 5 hours; the soaking agent is preferably deionized water.
[0051] In the present invention, the water used for washing is preferably deionized water, which is washed to neutrality.
[0052] In the present invention, the drying is preferably oven drying; the oven drying temperature is preferably 60 to 80° C., more preferably 65 to 75° C., and the heat preservation time is preferably 10 to 15 hours, more preferably 12 to 13 hours.
[0053] The present invention also provides a quaternary ammonium cellulose-based resin obtained by the preparation method described in the above scheme, comprising chlorine balls and quaternary ammonium cellulose modified on the surface of the chlorine balls.
[0054] In the present invention, the mass ratio of the chlorine balls to the quaternized cellulose is preferably 1 to 10:1, more preferably 2 to 8:1, and even more preferably 3 to 6:1.
[0055] The quaternized cellulose-based resin provided by the present invention is easy to recycle and can be used on a large scale, thus solving the problem that powdered adsorbents are difficult to recycle, and has good stability and excellent removal ability for perfluorinated substances in water.
[0056] The present invention also provides the use of the quaternary ammonium cellulose-based resin in the above scheme in water purification. The quaternary ammonium cellulose-based resin provided by the present invention has good adsorption performance and has an excellent removal effect on perfluorinated substances in water, especially drinking water, and can meet the latest "Sanitary Standards for Drinking Water" in my country.
[0057] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.
[0058] Example 1
[0059] (1) preparing a cellulose solution: obtaining Chinese medicine waste residue cellulose with reference to Chinese patent CN 117144707 A (a method for selectively extracting cellulose from Chinese medicine waste residue), and mixing the obtained Chinese medicine waste residue cellulose with water at a power of 1080 W for 20 min to obtain a cellulose solution; the raw material of the Chinese medicine waste residue cellulose is red peony root;
[0060] (2) adding sodium hydroxide, urea and distilled water to the cellulose solution, stirring to dissolve, precooling the resulting aqueous solution to -20°C in a refrigerator for 3 hours, and then immediately stirring vigorously at 25°C at 600 rpm for 15 minutes to obtain a cellulose solution;
[0061] The mass ratio of cellulose to urea in the cellulose solution is 1:55; the mass ratio of cellulose to sodium hydroxide in the cellulose solution is 1:37; the mass ratio of urea to distilled water is 1:7;
[0062] (3) 3-chloro-2-hydroxypropyltrimethylammonium chloride and cellulose units in the cellulose solution are added dropwise to the cellulose solution at a molar ratio of 40:1 at a rate of 60 drops / min, and stirred and mixed at 25° C. for 16 hours, the obtained quaternized cellulose solution is added to a reactor, and then chlorine balls with a particle size of 0.63 to 1.25 mm are added, and the reaction is carried out at 120° C. for 12 hours, and the obtained product is repeatedly washed with deionized water until it is neutral, and then soaked in deionized water for 5 hours, and dried to obtain a quaternized cellulose-based resin;
[0063] The mass ratio of the chlorine balls to the quaternized cellulose is 5:1.
[0064] Example 2
[0065] (1) Preparation of cellulose solution: same as in Example 1;
[0066] (2) adding sodium hydroxide, urea and distilled water to the cellulose solution, stirring to dissolve, storing the resulting aqueous solution in a refrigerator precooled to -15°C for 5 hours, and then immediately stirring vigorously at 30°C at 800 rpm for 10 minutes to obtain a cellulose solution;
[0067] The mass ratio of cellulose to urea in the cellulose solution is 1:55; the mass ratio of cellulose to sodium hydroxide in the cellulose solution is 1:37; the mass ratio of urea to distilled water is 1:7;
[0068] (3) 3-chloro-2-hydroxypropyltrimethylammonium chloride and cellulose units in the cellulose solution are added dropwise to the cellulose solution at a molar ratio of 40:1 at a rate of 60 drops / min, and stirred and mixed at 35° C. for 12 hours, the obtained quaternary ammonium cellulose solution is added to a reactor, and then chlorine balls with a particle size of 0.63 to 1.25 mm are added, and the reaction is carried out at 120° C. for 12 hours, and the obtained product is soaked in deionized water for 4 hours, repeatedly washed with deionized water until neutral, and then dried to obtain a quaternary ammonium cellulose-based resin;
[0069] The mass ratio of the chlorine balls to the quaternized cellulose is 5:1.
[0070] Example 3
[0071] (1) Preparation method of cellulose solution: same as in Example 1;
[0072] (2) adding sodium hydroxide, urea and distilled water to the cellulose solution, stirring to dissolve, storing the resulting aqueous solution in a refrigerator precooled to -25°C for 2 hours, and then immediately stirring vigorously at 35°C at a speed of 1000 rpm for 5 minutes to obtain a cellulose solution;
[0073] The mass ratio of cellulose to urea in the cellulose solution is 1:55; the mass ratio of cellulose to sodium hydroxide in the cellulose solution is 1:37; the mass ratio of urea to distilled water is 1:7;
[0074] (3) 3-chloro-2-hydroxypropyltrimethylammonium chloride and cellulose units in the cellulose solution are added dropwise to the cellulose solution at a molar ratio of 40:1 at a rate of 60 drops / min, and stirred and mixed at 45° C. for 12 hours, the obtained quaternized cellulose solution is added to a reactor, and then chlorine balls with a particle size of 0.63 to 1.25 mm are added, and the reaction is carried out at 120° C. for 15 hours, and the obtained product is soaked in deionized water for 8 hours, repeatedly washed with deionized water until neutral, and then dried to obtain a quaternized cellulose-based resin;
[0075] The mass ratio of the chlorine balls to the quaternized cellulose is 5:1.
[0076] Example 4
[0077] The preparation method of this embodiment is the same as that of embodiment 1, the only difference being that the precooling temperature is -50°C and the insulation time is 1 hour.
[0078] Example 5
[0079] The preparation method of this embodiment is the same as that of embodiment 1, the only difference being that the precooling temperature is -10°C and the insulation time is 5 hours.
[0080] Example 6
[0081] The preparation method of this embodiment is the same as that of embodiment 1, except that chlorine balls are added and the reaction is carried out at 100° C. for 15 h.
[0082] Example 7
[0083] The preparation method of this embodiment is the same as that of embodiment 1, except that chlorine balls are added and the reaction is carried out at 150° C. for 10 h.
[0084] Comparative Example 1
[0085] (1) Preparation method of cellulose solution: same as in Example 1;
[0086] (2) adding sodium hydroxide, urea and distilled water to the cellulose solution, stirring to dissolve, precooling the resulting aqueous solution to -20°C in a refrigerator for 3 hours, and then immediately stirring vigorously at 25°C at 600 rpm for 15 minutes to obtain a cellulose solution;
[0087] The mass ratio of cellulose to urea in the cellulose solution is 1:55; the mass ratio of cellulose to sodium hydroxide in the cellulose solution is 1:37; the mass ratio of urea to distilled water is 1:7;
[0088] (3) 3-chloro-2-hydroxypropyltrimethylammonium chloride and cellulose units in a cellulose solution are mixed at a molar ratio of 5:1 and stirred at 25° C. for 16 h, the resulting quaternized cellulose solution is added to a reactor, and then chlorine balls with a particle size of 0.63 to 1.25 mm are added, and the reaction is carried out at 120° C. for 12 h, and the resulting product is soaked in deionized water for 5 h, repeatedly washed with deionized water until neutral, and then dried to obtain a quaternized cellulose-based resin;
[0089] The mass ratio of the chlorine balls to the quaternized cellulose is 5:1.
[0090] Comparative Example 2
[0091] (1) Preparation method of cellulose solution: same as in Example 1;
[0092] (2) adding sodium hydroxide, urea and distilled water to the cellulose solution, stirring to dissolve, precooling the resulting aqueous solution to -20°C in a refrigerator for 3 hours, and then immediately stirring vigorously at 25°C at 600 rpm for 15 minutes to obtain a cellulose solution;
[0093] The mass ratio of cellulose to urea in the cellulose solution is 1:55; the mass ratio of cellulose to sodium hydroxide in the cellulose solution is 1:37; the mass ratio of urea to distilled water is 1:7;
[0094] (3) 3-chloro-2-hydroxypropyltrimethylammonium chloride and cellulose units in a cellulose solution are mixed at a molar ratio of 10:1 and stirred at 25° C. for 16 hours, the resulting quaternized cellulose solution is added to a reactor, and then chlorine balls with a particle size of 0.63 to 1.25 mm are added, and the reaction is carried out at 120° C. for 12 hours, and the resulting product is soaked in deionized water for 5 hours, repeatedly washed with deionized water until neutral, and then dried to obtain a quaternized cellulose-based resin;
[0095] The mass ratio of the chlorine balls to the quaternized cellulose is 5:1.
[0096] Comparative Example 3
[0097] (1) Preparation method of cellulose solution: same as in Example 1;
[0098] (2) adding sodium hydroxide, urea and distilled water to the cellulose solution, stirring to dissolve, precooling the resulting aqueous solution to -20°C in a refrigerator for 3 hours, and then immediately stirring vigorously at 25°C at 600 rpm for 15 minutes to obtain a cellulose solution;
[0099] The mass ratio of cellulose to urea in the cellulose solution is 1:55; the mass ratio of cellulose to sodium hydroxide in the cellulose solution is 1:37; the mass ratio of urea to distilled water is 1:7;
[0100] (3) 3-chloro-2-hydroxypropyltrimethylammonium chloride and cellulose units in a cellulose solution are mixed at a molar ratio of 20:1 and stirred at 25° C. for 16 h, the resulting quaternized cellulose solution is added to a reactor, and then chlorine balls with a particle size of 0.63 to 1.25 mm are added, and the reaction is carried out at 120° C. for 12 h, and the resulting product is soaked in deionized water for 5 h, repeatedly washed with deionized water until neutral, and then dried to obtain a quaternized cellulose-based resin;
[0101] The mass ratio of the chlorine balls to the quaternized cellulose is 5:1.
[0102] Comparative Example 4
[0103] A 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution with the same concentration as in Example 1 was prepared, and the 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution and chlorine balls with a particle size of 0.63-1.25 mm were added to a reaction kettle, and the reaction was carried out at 120° C. for 12 h. The obtained product was soaked in deionized water for 5 h, and repeatedly washed with deionized water until neutral, and then dried to obtain a quaternary ammonium resin;
[0104] The mass ratio of the chlorine ball to the 3-chloro-2-hydroxypropyltrimethylammonium chloride in the 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution is 15:1.
[0105] The quaternized cellulose-based resin prepared in Example 1 of the present invention was tested using a scanning electron microscope. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that the surface of the original chlorine ball is relatively smooth, the surface of the quaternized cellulose-based resin becomes rough, and the particles grafted on the surface of the chlorine ball are clearly observed, indicating that the quaternized cellulose has been successfully grafted and modified onto the surface of the chlorine ball.
[0106] The quaternized cellulose-based resin prepared in Example 1 of the present invention was tested by infrared spectroscopy. The results are as follows: Figure 2 As shown. Figure 2 It can be seen that the quaternized cellulose-based resin has a -1 A new peak appeared at 1640 cm -1 The peak at 1414 cm -1 The peak at 1112 cm is called CN stretching vibration. Compared with the original chlorine ball spectrum, the quaternary ammonium cellulose-based resin spectrum -1 and 1043cm -1 The increase in NH4+ provided evidence of etherification, indicating that the quaternary ammonium groups had been successfully incorporated into the cellulose backbone.
[0107] The original chlorine balls and quaternized cellulose-based resin in Example 1 of the present invention and the quaternized resin prepared in Comparative Example 4 were tested for PFAS removal. The test conditions were: PFAS concentration of 10 μg / L, adsorbent concentration of 0.5 g / L, rotation speed of 180 rpm, temperature of 25°C. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the original chlorine balls cannot effectively remove PFAS, and the quaternized ammonium resin prepared in Comparative Example 4 cannot remove PFAS well either. However, the quaternized cellulose-based resin provided by the present invention can remove PFAS well, reaching the latest "Sanitary Standards for Drinking Water" in my country, verifying the effectiveness of the preparation method provided by the present invention.
[0108] The quaternized cellulose-based resins prepared in Comparative Examples 1 to 3 of the present invention were tested for removing PFAS. The results are as follows: Figure 4 As shown. Figure 4 It can be seen that as the ratio of quaternary ammonium salt and cellulose units increases, the removal effect of PFAS becomes better, and the best and most stable removal effect is achieved when the molar ratio of quaternary ammonium salt and cellulose units is 40.
[0109] The quaternized cellulose-based resin prepared in Example 1 of the present invention was subjected to a kinetic test for the removal of perfluorooctanoic acid (a) and perfluorooctane sulfonic acid (b). The test conditions were: the concentration of PFAS was 1 μg / L, the concentration of the adsorbent was 1 g / L, and the adsorption time was 24 h. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that under environmentally relevant low concentrations of PFOA / PFOS, the adsorption rate of PFOA by quaternary ammonium cellulose-based resin is faster than that of PFOS, with PFOA reaching equilibrium in about 2 hours and PFOS reaching equilibrium in about 5 hours. This may be related to the fact that PFOS has one more fluorocarbon chain than the PFOA molecule and is more hydrophobic than PFOA. Quaternary ammonium cellulose-based resin removes PFAS mainly through electrostatic interactions, so it adsorbs PFOA faster than PFOS. In addition, it is also related to the pore structure and specific surface area of the material.
[0110] It can be seen from the above embodiments that the quaternized cellulose-based resin provided by the present invention can effectively remove trace PFAS in water bodies, and it is easy to recycle, which solves the problem that traditional powder adsorbents are difficult to recycle and scale up, and has broad application prospects.
[0111] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a quaternary ammonium cellulose-based resin, characterized in that: The following steps are involved: (1) mixing a cellulose solution, sodium hydroxide, urea and water, and then precooling and high-speed mixing in sequence to obtain a cellulose solution; the rotation speed of the high-speed mixing is 500 to 1000 rpm; (2) mixing an aqueous solution of 3-chloro-2-hydroxypropyltrimethylammonium chloride and the cellulose solution to carry out a quaternization reaction to obtain a quaternized cellulose solution; (3) The quaternary ammonium cellulose solution and chlorine balls are mixed for high temperature reaction, wherein the particle size of the chlorine balls is 0.315 to 1.250 mm and the temperature of the high temperature reaction is 100 to 150° C. to obtain a quaternary ammonium cellulose-based resin.
2. The preparation method according to claim 1, characterized in that: The cellulose solution comprises cellulose and water; The mass ratio of cellulose to urea in the cellulose solution is 1:25-100; The mass ratio of cellulose to sodium hydroxide in the cellulose solution is 1:25-100; The mass ratio of urea to water is 1:2-11.
3. The preparation method according to claim 1 or 2, characterized in that: The precooling temperature is -10 to -50°C, and the insulation time is 1 to 5 hours.
4. The preparation method according to claim 1, characterized in that: The molar ratio of 3-chloro-2-hydroxypropyltrimethylammonium chloride in the 3-chloro-2-hydroxypropyltrimethylammonium chloride aqueous solution to cellulose units in the cellulose solution is 5 to 50:
1.
5. The preparation method according to claim 1 or 4, characterized in that: The temperature of the quaternization reaction is 20-50° C., and the insulation time is 12-20 hours.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the chlorine balls to the quaternary ammonium cellulose is 1 to 10:
1.
7. The preparation method according to claim 1 or 6, characterized in that: The heat preservation time of the high temperature reaction is 10 to 15 hours.
8. The quaternized cellulose-based resin obtained by the preparation method according to any one of claims 1 to 7, characterized in that: The invention comprises a chlorine ball and quaternary ammonium cellulose modified on the surface of the chlorine ball.
9. The quaternized cellulose-based resin according to claim 8, characterized in that The mass ratio of the chlorine balls to the quaternary ammonium cellulose is 1 to 10:
1.
10. Use of the quaternized cellulose-based resin according to any one of claims 8 to 9 in water purification.
Citation Information
Patent Citations
Method for selectively extracting cellulose from traditional Chinese medicine residues through oxidation
CN117144707A
Method for Preparing Magnetically-Responsive Aminated Cellulose-Based Material for Adsorption of Heavy Metals and Application Method Thereof
AU2020101505A4
Quaternization cellulose bead as well as preparation method and application thereof
CN107522877A